Individual and job based determinants of performance appraisal: evidence from Germany - Christian Grund; Dirk Sliwka (Institute for the Study of Labor (IZA), 2007)
We investigate the use of performance appraisal (PA) in German Firms. First, we derive hypotheses on individual and job based determinants of PA usage. Based on a representative German data set on individual employees, we test these hypotheses and also explore the impact of PA on performance pay and further career prospects. The results include that PA is positively linked to an individual's willingness to take risks. The performance of older employees and woman is evaluated less often. Furthermore, larger firms evaluate the performance of their employees more. We find evidence for a non-monotonic relation between the hierarchical level and usage of performance appraisal: The performance of employees with very high or very low responsibilities is assessed less often.
Keywords: 650; Performance appraisal; performance evaluation; GSOEP; Personalbeurteilung; Arbeitsbewertung; Leistungsorientierte Vergütung; Erwerbsverlauf; Deutschland